ESPOUSING ABORTION RIGHTS: A CASE STUDY ON THE SATANIC TEMPLE - Tasin, Lydian Florina; Munjid, Achmad; Adhitya, Galant Nanta (Pengkajian Amerika, Universitas Gadjah Mada, 2023)
This study examines how a nontheistic organization called The Satanic Temple (TST) fights for religious freedom for its members, particularly in abortion rights in the US. Ronald Inglehart’s secularization framework is employed to conduct a more in-depth analysis of this group’s efforts to voice religious freedom for its members, particularly on the abortion issue. Therefore, this study also provides an in-depth examination of TST’s strategies regarding the abortion issue. The finding shows that TST has far-reaching implications not only for their efforts against the new abortion law but also for the group’s presence amidst the religious majority environment of the US. Furthermore, another finding also reveals that TST’s efforts in legal proceedings have yet to be treated fairly. TST has a strong legal argument because TST members interpret their fundamental tenets and have an abortion ritual. However, solid legal opinions are not always sufficient. In response to legal challenges, judges have shown reluctance to evaluate Satanist claims on their merits, preferring to invent procedural criticisms. The ruling did not hinder TST as much as it prevented the problem.